Custom-made endofemoral sleeves in knee revision surgery: case report and technical notes - Cavagnaro, Luca; Chiarlone, Francesco; Mosconi, Lorenzo; Sermi, Niccolò; Felli, Lamberto; Burastero, Giorgio (Lo Scalpello - Journal, 2021)
Revision total knee arthroplasty is a challenging procedure for every orthopaedic surgeon, especially when a megaprosthesis is involved. Possible surgical solutions in case of distal femur megaprosthesis revision are total femoral replacement (TFR) or amputation/disarticulation. TFR is affected by an extremely high rate of complications, while amputation/ disarticulation leads to unacceptable functional results. We report the case of a 59-year-old woman who underwent a staged left knee megaprosthesis revision for infection with massive femoral and tibial bone loss and complete disruption of extensor mechanism following 7 prior surgeries. To manage these problems, we developed a new, custom porous titanium endofemoral sleeve for the femoral side and a custom porous titanium cone for tibial reconstruction that were tailored to the patient’s specific bone loss and matched with the tumor prosthetic design used. A custom-made endofemoral sleeve may be a viable solution introducing an intermediate step between distal femur megaprosthesis and total femur substitution. Accurate and detailed surgical planning as well as intraoperative management of soft tissues and residual bone stock are key factors for optimal outcomes.